Oral Snuff and Carcinoma Oesophagus - Abdul Majeed Khan; Mohammad Shoaib Khan; Najib ul Haq (Gomal Journal of Medical Sciences, 2004)
Background: Carcinoma oesophagus is known to occur worldwide. Various dietary, environmental and genetic factors and certain pre-malignant conditions have been blamed in the causation of carcinoma oesophagus but the exact cause in unknown. This study was conducted to find out the possible role of oral snuff to carcinoma oesophagus.